Supporting mental health: pre-post four-week psychological capacity building program for Indian target sport athletes - Gill, S.; Singh, P. (Human Movement, 2024)
Purpose: Mental training, widely recognised in sports psychology, has not been fully utilised to address broader mental health concerns among athletes, especially in India. This study examines the Psychological Capacity Building Program (PCB P) for Indian shooters and archers, focusing on key psychological variables such as motivation, grit, emotions, and well-being. The four-phase program includes sports analyses, individual assessments, motivational tasks, a one-week psychoeducational phase on mental skills, and two weeks of applying these skills in the athlete`s daily training routines.